Spinal Cord Suspension Using Dentate Ligament Hitch Stitches: A Novel Technique for the Repair of Ventral Spinal Cord Herniation. Issue 3 (9th May 2017) - Lui, Jonathan; Sayal, Parag; Choi, David
Abstract: BACKGROUND: Idiopathic spinal cord herniation is usually repaired by releasing the spinal cord and inserting a dural patch to close the herniated segment of dura. However, reherniation is a potential limitation of this standard technique. OBJECTIVE: To describe early results of a novel technique that utilizes the dentate ligament to hitch the spinal cord and prevent reherniation. METHODS: Two patients underwent dural hernia repair and the dentate hitch technique was performed. RESULTS: Restored lower limb power and mobility, and satisfactory reduction of spinal cord herniation on magnetic resonance imaging in 2 patients at 6- and 24-mo follow-ups, respectively. CONCLUSION: The dentate hitch technique can achieve repair of spinal cord herniation, with satisfactory postoperative results and minimizes the risk of reherniation.